2020
DOI: 10.1530/rep-20-0271
|View full text |Cite
|
Sign up to set email alerts
|

Maternal iron homeostasis: effect on placental development and function

Abstract: Iron is an essential mineral that participates in oxygen transport, DNA synthesis and repair, and as a cofactor for various cellular processes. Iron deficiency is the most common nutritional deficiency worldwide. Due to blood volume expansion and demands from the fetal-placental unit, pregnant women are one of the populations most at risk of developing iron deficiency. Iron deficiency during pregnancy poses major health concerns for offspring, including intrauterine growth restriction and long-term health comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Likewise, the iron concentrations in the cord blood were much lower than that in full-term births, revealing remarkable iron deficiency in the developing fetuses prior to preterm births ( Figure 1(d) ), P < 0.001). Previous animal studies have portrayed the placenta as a selfish organ since the placenta stores an adequate amount of iron to ensure its functions in maternal iron deficiency [ 13 ]. However, a recent study conducted by Irwinda et al indicated that the placental iron stores in women with preterm births were much lower than that in women full-term births [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Likewise, the iron concentrations in the cord blood were much lower than that in full-term births, revealing remarkable iron deficiency in the developing fetuses prior to preterm births ( Figure 1(d) ), P < 0.001). Previous animal studies have portrayed the placenta as a selfish organ since the placenta stores an adequate amount of iron to ensure its functions in maternal iron deficiency [ 13 ]. However, a recent study conducted by Irwinda et al indicated that the placental iron stores in women with preterm births were much lower than that in women full-term births [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Greatly decreased placental iron stores were found in participants with preterm births relative to those with full-term births as evidenced by decreased placental tissue iron ( Figure 1(e) ), P < 0.05) and diminished mass of ferritin ( Figure 2(c) ), P < 0.05). Despite no direct experimental evidence, the maternal hepcidin is assumed to control the placental iron transport through syncytiotrophoblasts [ 13 , 36 , 37 ]. The mass of FPN in placentas was greatly elevated in the preterm group, compared to the full-term group ( Figure 2(c) ), P < 0.05) presumably attributable to the diminished maternal hepcidin levels ( Figure 2(b) ), P < 0.001), implying a direct regulation of maternal hepcidin on the FPN concentrations in syncytiotrophoblasts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most animal models of diet‐induced ID have found that placental weight and diameter do not significantly differ between iron‐deficient animals or animals with an adequate iron intake 14,47 . However, one study of dietary‐iron‐restricted rats found that, although maternal iron restriction had no effect on placental weight at gestational day 13.5—the equivalent of a human second trimester—it did result in a 10% increase in placental weight at term and that this effect was mainly seen via an expansion in the junctional zone of the placenta 43 . We did not find convincing evidence of human studies supporting these results, with only a small cross‐sectional study of women delivering healthy term babies seeming to show a nonsignificant decrease in weight between placentas from women with low serum ferritin ( n = 26; mean ferritin 7.65 ± 1.28 μg/L; placental weight 0.59 ± 0.13 kg) versus those with normal serum ferritin ( n = 18; mean ferritin 34.2 ± 12.8 μg/L; placental weight 0.65 ± 0.21 kg) 48 …”
Section: Maternal Iron Deficiency and The Placentamentioning
confidence: 99%